Dynamic Chemistry-Based Sensing: A Molecular System for Detection of Saccharide, Formaldehyde, and the Silver Ion - Chang, Xingmao; Wang, Zhaolong; Qi, Yanyu; Kang, Rui; Cui, Xinwen; Shang, Congdi; Liu, Kaiqiang; Fang, Yu (Analytical chemistry (Washington), 2017)
Development of artificial complex molecular systems is of great importance in understanding complexity in natural processes and for achieving new functionalities. One of the strategies is to create them via optimized utilization of noncovalent interactions and dynamic covalent bonds. We report here on a new complex molecular system, which was constructed by integrating the multiple interactions containing a dynamic covalent interaction between 1,2-diol and boronic acid, a coordination interaction between the silver ion and pyridyl, and an easy accessible reaction between secondary amine and formaldehyde. By employing the three dynamic interactions, a pyrene (Py) labeled fluorophore, PPB, was designed and synthesized. The compound reacts with fructose (F), a monosaccharide, in aqueous phase and produces a fluorescent adduct, PPB-F, which can be further used as a sensing platform for formaldehyde (FA) and the silver ion. The respective dynamic interactions are accompanied with color changes due to the reversible switching between Py-monomer emission and excimer emission. The respective experimental detection limits (DLs) for the three analytes are much lower than 0.2 mM, 0.1 mM, and 2.5 μM, respectively. The presence of relevant compounds or ions shows little effect upon the sensing. No doubt, the results as presented show that the integration of supramolecular interactions including dynamic covalent bonds can be employed as a general strategy to develop new functional molecular systems or materials.